COEFFICIENT OF VARIATION: A NEW APPROACH FOR THE STUDY IN MAIZE EXPERIMENTS: Coefficient of variation: a new approach - NARDINO, Maicon; PEREIRA, Juliana Machado; MARQUES, Vinícius Torres; D’AVILA, Fabiano Costa; FRANCO, Francisco​ Dias; BARROS, Willian Silva (Brazilian Journal of Biometrics, 2020)
The magnitude of the variation coefficient (CV) is insufficient to validate the quality of the experiment, regardless of the number of treatments, repetitions and effect of treatments. The objective was to develop a new approach to the study of coefficient of variation, as well as evaluations of these nuances with applicability in new scientific research. The study was conducted via computer simulation. The replicates (r) ranged from 2, 3, 4, 5, 10 to 20. The treatment number (t) ranged from t 5, 10, 15, 20, 25 and 30. In each of these combined scenarios we have the variation of 25 different CVs, ranging from 1, 3, 5, 7, ..., 49 to 51 %. It was imposed the variation of 11-1 treatment effects 0, 240, 480, 720, ..., 2000, 2400 kg ha-1, totaling 9,900.00 scenarios. The type I error is statistically invariant in the scenarios studied. With high treatment effect the CV has no implications on the power of the test (1-β). The results obtained in this research reveal that experiments with a high percentage of CV are sufficient to obtain high probabilities of the power of the F test, which do not compromise the complementary analyzes.